2016
DOI: 10.1016/j.contraception.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical administration of polidocanol foam prevents pregnancy in female baboons

Abstract: BackgroundOur objective was to conduct a pilot study to determine if transcervical administration of polidocanol foam (PF) with or without doxycycline or benzalkonium chloride (BZK) would prevent pregnancy in baboons.MethodsIn study phase 1, adult cycling baboons underwent a hysterosalpingogram to evaluate tubal patency prior to transcervical infusion of 20 mL of 5% PF followed by 1 mL of saline containing 100 mg doxycycline (5%/doxy; n=5), 3% PF plus doxycycline (3%/doxy; n=4), 3% PF with 0.01% BZK (3%/BZK; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
0
15
1
1
Order By: Relevance
“…Sinha found that secretory phase timing reduced the success of placement of Essure ™ microinserts . In support of research evaluating non‐surgical approaches to PC, we performed HSGs in female baboons prior to other transcervical procedures . During the course of these studies, we noted differences in the success of our tubal imaging based on cycle timing and hormonal treatment.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Sinha found that secretory phase timing reduced the success of placement of Essure ™ microinserts . In support of research evaluating non‐surgical approaches to PC, we performed HSGs in female baboons prior to other transcervical procedures . During the course of these studies, we noted differences in the success of our tubal imaging based on cycle timing and hormonal treatment.…”
Section: Introductionmentioning
confidence: 79%
“…Between October 2012 and November 2016, we completed several studies investigating approaches to non‐surgical permanent contraception in women at SNPRC and ONPRC using the baboon model. Results from some of these studies have previously been reported and others are ongoing . We performed one or more baseline hysterosalpingogram procedures and serum sampling for estradiol and progesterone prior to the investigational treatment in 110 healthy adult (ages 5—16 years) female baboons (Papio anubis n = 62, [SNPRC]; Papio hamadryas n = 48, [ONPRC]).…”
Section: Methodsmentioning
confidence: 99%
“…Cesarean sections were performed at 165±3 days of gestation, as confirmed by a Doppler sonography evaluation. This gestational age is near-term in baboons [ 20 ], and results in viable neonates [ 21 ]. Cesarean section surgery was performed using standard methodology that included maternal anesthesia (induction with ketamine hydrochloride, 10 mg/kg of body weight, and maintenance with 1.5–2% isoflurane).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, primate studies have found that a single intrauterine dose of polidocanol foam administered transcervically has high rates of tubal occlusion. 9 Other methods in early development include the intrauterine injection of a degradable polymer to induce tubal blockage (FemBloc).…”
Section: Permanent Sterilizationmentioning
confidence: 99%